The Role Of Service Quality In Affecting Customer Satisfaction: The Mediating Role Of Customer Value - Zulganef Zulganef; Cucu Hodijah (Jurnal Manajerial, 2023)
Background – In service sector, there is always a possibility for customers to selectively choose their desired service that will meet their satisfaction. Organizations are thus required to identify the factors that determine customer satisfaction. Aim – This study aims to investigate the mediating effect of customer value on the relationship between service quality and customer satisfaction at the library of Widyatama University, Bandung, Indonesia. Design/ Methodology/ Approach – Using quantitative approach, this study distributed 800 questionnaires to respondents, and receive 713 questionnaires that can be used for further analysis. The data analysis is carried out using structural equation modeling (SEM) with AMOS. Findings – This study shows that customer value has no effect on satisfaction, meaning that customer value does not play a role in mediating the relationship between service quality and satisfaction. Only two variables based on dimensions of Service Quality Analysis (SERVQUAL) have an effect on other variables, namely assurance and empathy. Conclusion - Customer value and satisfaction for library users at Widyatama University are two different things that have no relationship or connection at all. The service quality variable that affects customer value is assurance, while the variable that affects satisfaction is empathy. Research implication – There are two things that must be considered by the library manager, namely the assurance perceived by library users, and the empathy that the library’s managers and staff must have, especially as the providers of library service. Limitations – This research was only conducted in one university library, so the results about the condition of the library or services cannot be generalized. It also only utilizes the two-dimensional model of SERVQUAL, thus future research are required to address and develop this topic.